Constrained Interpolation Profile Conservative Semi-Lagrangian Scheme Based on Third-Order Polynomial Functions and Essentially Non-Oscillatory (CIP-CSL3ENO) Scheme (Communications in Computational Physics, 2017)
We propose a fully conservative and less oscillatory multi-moment schemefor the approximation of hyperbolic conservation laws. The proposed scheme (CIP-CSL3ENO)is based on two CIP-CSL3 schemes and the essentially non-oscillatory(ENO) scheme. In this paper, we also propose an ENO indicator for the multi-momentframework, which intentionally selects non-smooth stencil but can efficientlyminimize numerical oscillations. The proposed scheme is validated through variousbenchmark problems and a comparison with an experiment of two droplets collision/separation.The CIP-CSL3ENO scheme shows approximately fourth-order accuracyfor smooth solution, and captures discontinuities and smooth solutions simultaneouslywithout numerical oscillations for solutions which include discontinuities.The numerical results of two droplets collision/separation (3D free surface flow simulation)show that the CIP-CSL3ENO scheme can be applied to various types of fluidproblems not only compressible flow problems but also incompressible and 3D freesurface flow problems.